Does a fighter pilot live in the danger zone? A risk assessment applied to military aviation - Daniel Alberto Pamplona; Claudio Jorge Pinto Alves (Transportation Research Interdisciplinary Perspectives, 2020)
Military aviation is different compared to civil aviation. The two main differences are the operational environment and aircraft characteristics. The United States Air Force (USAF) conducts a range of military operations from rescue missions to full-scale war environments. Military aviation, because of its operational environment and aircraft characteristics, works under frequent risk. This paper investigates the probability of accidents occurring among the current USAF's fleet and classifies which aircraft is the most dangerous to fly. After performing goodness-of-fit tests using historical data, a Gamma-Poisson probability distribution is used to model the probability of Class A mishaps, Class B mishaps, and Fatalities. The results show that three aircraft have a probability >20% of one fatality occurring. These three aircraft are classified in the study as “The 20% Club,” and the pilots of these aircraft are exposed to higher risks during operations compared to other military aircraft. The results showed that fighter pilots, due to the nature of their missions, have a higher probability of incidents, accidents, and fatalities occurring. However, the results also show that fighter pilots are not the only ones who face a constant risk; transport and training aircraft also presented a high probability of accidents or fatalities, showing how risky military aviation is.